1990
DOI: 10.1007/bf01541932
|View full text |Cite
|
Sign up to set email alerts
|

Sexual attitudes in the Chinese

Abstract: The sexual attitudes in the Chinese have been described by scholars as suppressive or nonsuppressive, based on observations made on various aspects of the Chinese culture. Many characteristics of the Chinese history and society are responsible for this controversy and confusion. The overall picture may be better understood using the developmental model propounded by some modern sociologists in the study of social units and collective behaviors. It is time to proceed from static to dynamic to try to apply this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 10 publications
0
46
0
Order By: Relevance
“…It has been well documented that, relative to North American standards, Chinese culture places a greater emphasis on propriety, and the observance of strict moral and social codes (Ng and Lau, 1990). Many authors have suggested this social conservatism has led to the suppression of sexual needs and expression among the Chinese people (e.g., Suen, 1983;Tseng and Hsu, 1970).…”
Section: Asian Versus Non-asian Differences In Sexual Behaviormentioning
confidence: 98%
“…It has been well documented that, relative to North American standards, Chinese culture places a greater emphasis on propriety, and the observance of strict moral and social codes (Ng and Lau, 1990). Many authors have suggested this social conservatism has led to the suppression of sexual needs and expression among the Chinese people (e.g., Suen, 1983;Tseng and Hsu, 1970).…”
Section: Asian Versus Non-asian Differences In Sexual Behaviormentioning
confidence: 98%
“…Individuals of Asian descent comprise one of the fastest growing ethnic groups in both countries. However, there exist philosophical differences, with long historical roots, between Asian and North American cultures regarding family structure and interpersonal relations, which may lead to the adoption of different beliefs as to the meaning of sexual activity (Ng & Lau, 1990). For instance, the acceptance of sexual behavior as procreative in Asian culture versus the North American view of sexuality as recreative is one example of how conflict between belief systems may have significant implications on the individual.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, the classic Yin-Yang doctrine I-Ching (Book of Changes) of 1150-249 BC viewed sex as an integral and essential element of nature where man and woman function as two natural forces that are constantly striving for harmony (Ng & Lau, 1990). Taoism regarded appropriate sexual behavior as a contributor to health and longevity, and Confucianism viewed sexual impulse as reflecting the natural order of fulfilling one's filial obligation of marriage, and producing children (Ruan, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Since the Open Door policies in the 1970s and the economic reforms of the 1980s, attitudes towards sexuality in China have changed (Zhang & Beck, 1999), premarital sexual intercourse appears more and more frequently among young people and people in China are now more tolerant toward extramarital sexual behaviors. In some former studies, the sexual attitudes in the Chinese have been described by scholars as suppressive or nonsuppressive, based on observations made on various aspects of the Chinese culture (Ng & Lau, 1990). During the age of information and globalization, sexual information, such as porn photographs and audio-visual products, is easy to get on mass media, and some western sexual attitudes are widely known by Chinese, especially Chinese college students.…”
Section: Introductionmentioning
confidence: 99%